IMPLICATIONS OF HEALTHCARE SYSTEM IN SINGAPORE AND MALAYSIA AS INTERESTING LESSONS TOWARDS PRIMARY SERVICE INNOVATION FOR INDONESIA - Annisa Purwatiningsih; Asih Widi Lestari; Lisa Dhuhaniyati (Prodi Sosiologi Agama, 2022)
Excellent service of health become a necessity for the community, even as a promising business opportunity today. Hospitals in Indonesia and hospitals abroad are competing to provide the best service for their patients. The comparison of the health care system and the quality of medical services in Indonesia is very different from that of Singapore and Malaysia. So that many patients from Indonesia go to Singapore and Malaysia for treatment. The causative factor is the perception of hospital services, medical personnel, doctors, and the quality of hospital services.Service innovation becomes excellent service that changes from time to time, lifestyle and life expectancy, so that the Quality Adjusted Life Year approach becomes the focus of prime quality health outcomes.